2019
DOI: 10.1101/550277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Egalitarian binding partners, Dynein Light Chain and Bicaudal-D, act sequentially to link mRNA to the Dynein motor

Abstract: A widely conserved mechanism of polarity establishment is the localization of mRNA to specific cellular regions. While it is clear that many mRNAs are transported to their destinations along microtubule tracks, much less is known regarding the mechanism by which these mRNAs are linked to microtubule motors. The RNA binding protein Egalitarian (Egl) is necessary for localization of several mRNAs in Drosophila oocytes and embryos. In addition to binding RNA, Egl also interacts with Dynein light chain (Dlc) and B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…In support of this model, we showed that artificially dimerizing a mutant version of Egl that could not associate with Dlc was sufficient to restore its ability to bind to mRNA and BicD. These experiments were conducted using lysates from Drosophila S2 cells (Goldman et al, 2019). An important question raised by this finding is whether artificially dimerizing Egl could rescue mutant phenotypes in vivo.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In support of this model, we showed that artificially dimerizing a mutant version of Egl that could not associate with Dlc was sufficient to restore its ability to bind to mRNA and BicD. These experiments were conducted using lysates from Drosophila S2 cells (Goldman et al, 2019). An important question raised by this finding is whether artificially dimerizing Egl could rescue mutant phenotypes in vivo.…”
Section: Introductionmentioning
confidence: 84%
“…The in vitro RNA binding experiments using ILS, TLS and GLS localization elements were performed as previously described (Dienstbier et al, 2009;Goldman et al, 2019).…”
Section: Rna Binding Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovaries were processed for in situ hybridization using a published protocol (Goldman et al, 2019). Dissected ovaries were fixed with 4% formaldehyde for 20 mins.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…Ovaries were processed for immunofluorescence using a previous described procedure (Goldman et al, 2019). Briefly, flies were fattened on yeast pellets for 3 days.…”
Section: Immunofluorescencementioning
confidence: 99%